Analysis of Students' Critical Thinking Abilities in Physics Learning: A Case Study at SMAN 5 Sidrap - Prabayanti, Eka; Usman, Usman; Khaeruddin, Khaeruddin; Setiawan, Trisno (Jurnal Pendidikan Fisika, 2024)
Critical thinking is one of the essential skills required of students in the 21st century. This research aims to provide an overview of students' critical thinking skills at in high school while studying the concept of Newton's Laws. Critical thinking skills refer to the cognitive processes employed by students to analyze and evaluate information effectively, enabling sound decision-making. The research method used is a descriptive-quantitative approach, involving a population of 130 students and a purposive sample of 60 students. Data were collected using a critical thinking test comprising 31 multiple-choice questions, addressing four indicators: interpretation, analysis, evaluation, and inference. The result of the study show that students' performance on the interpretation indicator predominantly fell into the low category, with 53.33%. Critical thinking skills for the analytical indicator were similarly low, at 38.33%. Critical thinking skills for evaluation were also categorized as low, at 43.33%. Meanwhile, critical thinking skills for inference were slightly better, being in the medium category at 46.67%. In general, students' critical thinking abilities at SMAN 5 Sidrap were primarily low, with 60% of students falling into this category. One of the factors causing students' poor critical thinking skills is the infrequent exposure to exercises designed to measure these skills. Therefore, implementing learning models that actively enhance critical thinking skills is essential.